Faktor yang Mempengaruhi Minat Belajar Bahasa Inggris Siswa di Salah Satu SMP Negeri di Jakarta - Mariana Damayanti; Irma Savitri Sadikin (STKIP Siliwangi, 2023)
The level of success students has in school is strongly influenced by how much they enjoy learning. The objectives of this study are to analyze what factors influence student interest in learning English and to find out what is the dominant factor that influence students’ interest in learning English. A mixed-method approach was employed to describe some factors and dominant factors that influence students’ interest in learning English. Students in the eighth grade at one public Junior High School in Jakarta, involving 279 participants, were surveyed and interviewed to collect data. The findings of this study indicated that internal factors, which consist of physical and non-physical aspects such as attention, readiness, and intelligence could influence students’ interest in learning English. Besides, external factors from outside the individuals, such as families, schools and peers contribute to their learning interests. The result revealed that the internal factors showed 68,93%, while external factors showed 59,34%. Therefore, the result indicated that the internal factor was higher than the external factor in influencing students’ interest in learning English. The most influencing in internal factors are psychological, namely intelligence, readiness, and attention, rather than physical factors.